RRI Purwokerto Rural Broadcasts in 1970-1990s - Prabasanti, Mustika Ratna (MOZAIK Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
AbstractThis research explores Rural Broadcasting of RRI Purwokerto in the 1970-1990s. Rural Broadcasting is a program to support the achievement of the national economic development program, particularly in the food security sector. The objective of this research is to reveal (1) the role of RRI Purwokerto as a broadcasting institution in implementing rural broadcasting programs, (2) observe the interest of the community in the Banyumas region and its surroundings towards rural broadcasting programs, and (3) explore the driving factors for success in implementing Rural Broadcasting of RRI Purwokerto, making it a pivotal program. The results of this research are as follows: (1) The implementation of Rural Broadcasting by RRI Purwokerto began on October 1, 1968, despite various limitations. Together with RRI Yogyakarta, RRI Purwokerto succeeded in pioneering the implementation of rural broadcasting in Indonesia. (2) The community's high interest is evident in its response with the formation of "kelompen" or "kelompencapir" as activity forums in various villages in the Banyumas Regency and its surroundings. (3) Creativity in broadcast products, the high work ethic of the managers, as well as collaboration with relevant institutions, are key factors for success, making rural broadcasting a pivotal program for RRI Purwokerto.Keywords: Rural Broadcasting, RRI Purwokerto, creativity, kelompen/ kelompencapir